The citrus leprosis pathosystem - Bastianel,Marinês (2006)
Citrus leprosis is considered the main viral disease for the Brazilian citrus production, particularly for the State of São Paulo, due to the high costs spent for the chemical control of its vector, the tenuipalpid mite Brevipalpus phoenicis. In addition, its global importance has significantly increased in the last years, with the dissemination of the virus to new countries in South and Central America. In Brazil, despite its economical importance and occurrence for more than seven decades, the most significant advances towards understanding the pathosystem interactions have been obtained only in the last ten years. This review focuses on various aspects of the disease, beginning with a historical view, its main characteristics, alternatives for its control, its increasing economical importance in Brazil and abroad, and the new data on the search for understanding the interactions amongst the mite vector, the virus, and the plant host.